Morfologia de frutos, sementes e plântulas de Lecythidoideae - Rodrigues, Lorena Patricia Figueira (Instituto Nacional Pesquisas da Amazônia - INPA, 2020)
The subfamily Lecythidoideae (Lecythidaceae) is exclusive to the Neotropics, with the largest number of species in the total for the family, ca. 234 species included in 10 genera. In Brazil there are 9 genera and a total of 118 species, 103 of which are found in the Amazon biome. Despite its high representativeness in the Amazon, there are few morphological studies for the group, mainly for seedlings. In this study, the objective was to conduct a morphological study of 31 species of nine genera of Lecythidoideae, collected in three locations north of Manaus (Area of Relevant Ecological Interest - Biological Dynamics Project of Forest Fragments; Adolpho Ducke Forest Reserve and at the Amazon Museum) ), expand the morphological information of fruits, seeds and seedlings for Amazonian species and its relevance for taxonomy. A database was generated of the newly collected material, the germination process and seedlings until the development of three to ten expanded leaves, addressing 217 quantitative and qualitative morphological characters (58 from fruits, 19 from seeds and 140 from seedlings). The first chapter contains the morphological descriptions of fruits, seeds and seedlings of 22 species of Lecythidoideae, including comments, identification keys and photographic plates, and the second chapter addresses the morphological diversity of the seedlings of 31 species of Lecythidoideae through multivariate analyzes. In chapter 1, the seedlings are bipolar germination, the hypocotyl stores reserves, the cotyledons are absent and the epicotyl − first-leaf-expanded axis has 3 to 14 cataphiles. The circumcised operculum for the fruits of Lecythis gracieana and L. prancei, and an undifferentiated embryo for the seeds of Allantoma decandra are new observations. In the seedlings, expanded leaves and cataphylls have decurrent stipules. In chapter 2, multivariate analyzes showed that due to the similarity of the cotyledons and hypocotyl, which is elongated, the genera Cariniana, Couratari and Couroupita are morphologically related. On the other hand, bipolar germination is present in Allantoma, Bertholletia, Corythophora, Eschweilera and Lecythis, so these genera are related morphologically by this character. The characters of the epicotyl − first-expanded-leaf axis are uniform in all groups of seedlings formed by species of Lecythidoideae, which can be considered a promising informative character for the group, from the taxonomic point of view. The variation in the germination pattern (unipolar vs. bipolar) separates the genera of this studied group, because Cariniana, Couratari and Couroupita present unipolar germination; and Allantoma, Bertholletia, Corythophora, Eschweilera and Lecythis bipolar germination. These characters are diagnostic for the subfamily Lecythidoideae. In addition to this initial characteristic of seedlings, we concluded that additional characteristics of fruit, seed and seedlings make it possible to more accurately identify genera and species. Considering that this study evaluated only 31 species of Neotropical Lecythidaceae, part of our findings, highlight morphological descriptions and unpublished illustrations for this group. These studies provide relevant information to support taxonomic studies, as well as species conservation.
Keywords: Lecythidoideae; Morfologia de propágulos; Polaridade na germinação; Taxonomia